Strategic repertoire variety and new venture growth: The moderating effects of origin and industry dynamism - Larrañeta, Bárbara; Zahra, Shaker A.; Galán González, José Luis (Strategic Management Journal, 2014)
New ventures (companies eight years or younger) face an important choice in attempting to achieve growth: Should they follow “strategic simplicity” by relying on a few similar competitive actions, or emphasize “strategic variety” by implementing multiple different competitive actions? Data from 140 new ventures in S pain suggest that new ventures benefit from pursuing strategic variety, especially when their industries are highly dynamic. Further, although new ventures in general gain from strategic variety in highly dynamic industries, independently owned ventures achieve higher growth rates than their corporate counterparts . Copyright © 2013 John Wiley & Sons, Ltd.